Analisa Pengelolaan Modal Kerja pada Perusahaan Industri Semen - Engelwati Gani (Bina Nusantara University, 2011)
The purpose of this research is to identify financial ratios, to analyse the relation among the financial ratios, and to compare financial ratios of PT Indocement Tunggal Prakarsa, Tbk., PT Semen Gresik (Persero), Tbk., dan PT Holcim Indonesia, Tbk. The research method is qualitative, descriptive research, with the research time dimention using time series. The research depth is using the three industrial cement companies that listed in Indonesia Stock Exchange (BEJ). The gathering data method is by indirect contact like archive data.